A preliminary report on the use of the wide angle diffuser in ground mufflers of the type used for silencing jet aircraft - Green, D. J. (College of Aeronautics, 1955)
Experiments with a model wide angle diffuser, in combination with suitable gauze resistances, fitted to the eLsci.t of a high velocity cold jet show that reductions in total noise level of greater than 30 db. can be achieved; the spectrum being flat. It is shown that the wide angle diffuser when fitted to the tail pipe of p. jet engine as a ground muffler need. not affect the characteristics of the engine during 'run up', Applications of this type of muffler to the silencing of jet engines during 'run .up', jet test beds and exhaust silencing of internal combustion engines are briefly discussed.